2019
DOI: 10.1158/0008-5472.can-19-1236
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BCR-ABL1 in Chronic Myeloid Leukemia by PROTAC-Mediated Targeted Protein Degradation

Abstract: While the use of ATP-competitive tyrosine kinase inhibitors of oncoprotein BCR-ABL1 has enabled durable responses in patients with chronic myeloid leukemia (CML), issues of drug resistance and residual leukemic stem cells remain. To test whether the degradation of BCR-ABL1 kinase could offer improved response, we developed a series of proteolysis targeting chimera (PROTACs) that allosterically target BCR-ABL1 protein and recruit the E3 ligase Von Hippel Lindau (VHL), resulting in ubiquitination and subsequent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(151 citation statements)
references
References 42 publications
1
149
0
1
Order By: Relevance
“…Western blotting conrmed the strong on-target activity of 34. As human and murine E3 ligase VHL is not completely conserved between different species, 66 we investigated whether the murine 32D and Ba/F3 cells constitute an appropriate model system for the effects of our VHL-based degraders. PROTAC 22 induced pronounced CDK6 degradation in both Ba/F3 and 32D cells at 1 mM, demonstrating activity in murine cells (Fig.…”
Section: Applicability In Different Cell Linesmentioning
confidence: 99%
“…Western blotting conrmed the strong on-target activity of 34. As human and murine E3 ligase VHL is not completely conserved between different species, 66 we investigated whether the murine 32D and Ba/F3 cells constitute an appropriate model system for the effects of our VHL-based degraders. PROTAC 22 induced pronounced CDK6 degradation in both Ba/F3 and 32D cells at 1 mM, demonstrating activity in murine cells (Fig.…”
Section: Applicability In Different Cell Linesmentioning
confidence: 99%
“…Pioneering studies by the Crews lab have shown that BCR-ABL PROTACs, consisting of CRBN or VHL recruiters linked to BCR-ABL ATP binding pocket-targeting kinase inhibitors such as dasatinib and bosutinib or allosteric inhibitors such as GNF-2, showed preferential degradation of c-ABL over modest degradation of BCR-ABL (Burslem et al, 2019;Lai et al, 2016). Notably, this work has spurred development of various degradation strategies targeting BCR-ABL (Demizu et al, 2016;Shibata et al, 2017Shibata et al, , 2019Shimokawa et al, 2017;Zhao et al, 2019).…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, EN219 showed preferential degradation of BCR-ABL compared to c-ABL, compared to several previous BCR-ABL degraders utilizing cereblon or VHL recruiters that showed opposite selectivity (Fig. 4b-4c) (Burslem et al, 2019;Lai et al, 2016). This preferential degradation was also observed with the equivalent nimbolide-based degrader 9 .…”
Section: En219-based Rnf114 Recruiter In Tpd Applicationsmentioning
confidence: 67%